AROMATASE INHIBITORY AND CYTOTOXIC ACTIVITIES OF CHEMICAL CONSTITUENTS FROM THE VIETNAMESE MEDICINAL PLANT BAN-CHI-LIEN (SCUTELLARIA BARBATA D. DON) - Do Thi Thao; Le Quang Huan; Do Khac Hieu; Nguyen Quyet Chien; Nguyen Van Hung (Universitas Gadjah Mada, 2008)
Aromatase inhibitory and cytotoxic activities were determined for apigenin, luteolin and the new diterpene named scutebarbalactone VN, which were obtained by bioassay-guided fractionation and isolation from the methanol extract of the Vietnamese medicinal plant Banchi-lien (Scutellaria barbata D. Don). In the aromatase inhibition assay, an IC50 value of 3.36 mM was found for scutebarbalactone VN, while IC50 values of 7.2 mM and 7.95 mM were found for the positive controls aminoglutethimide and b-estradiol, respectively. In the cytotoxicity assays using a panel of human cancer cell lines, scutebarbalactone VN showed promising anticancer activity with IC50 ranging from 2.15 to 8.3 mM compared with those of the positive control ellipticine ranging from 1.0 to 2.1 mM. Apigenin and luteolin were found to be inactive in both assays.